Analisis Pengaruh Inflasi Terhadap Tingkat Pengangguran Terbuka di Provinsi Sumatera Barat Tahun 2019-2023 - Tamala, Novi; Inaya, Iin; Aulia, Maya Nailatul; Nurtias, Satria; Desmawan, Deris (Jurnal Informatika, 2024)
This research is aimed at analyzing the effect of inflation on unemployment in West Sumatera province in 2019-2023. The problem of unemployment is a complex socio-economic issue. This is because unemployment does not just stand alone, but is continuous with many other indicators, for example inflation. The government is working hard to minimize this unemployment problem, and they will continue to be committed to eliminating it. Unemployment, as a complex socio-economic problem, is closely related to other indicators, such as the influence of inflation. This research is quantitative. The data was obtained from the BPS West Sumatera website. To analyze the data, the SPSS 2024 test was used. The research results showed that inflation could explain up to 67.8 percent of unemployment. This means that the unemployment rate in West Sumatera province is influenced by inflation.